2022
DOI: 10.1111/eve.13650
|View full text |Cite
|
Sign up to set email alerts
|

Otopathy secondary to trigeminal schwannoma in a Quarter Horse

Abstract: Otitis media secondary to trigeminal nerve (CN-V) paralysis is described in dogs and humans but not in horses. An 18-month-old Quarter Horse colt was presented with history of mastication difficulties and a nonhealing corneal ulcer. Clinical findings were consistent with paralysis of the right CN-V. Computed tomography imaging showed otopathy media and a mass at the root of the CN-V. The colt was euthanised due to poor prognosis. Postmortem magnetic resonance imaging showed enlargement of the right CN-V which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The main differentials for the mass seen on CT were neoplastic, inflammatory, or infectious. Previous case reports of horses with masses in close proximity with the cranial nerves have described multiple differing diagnoses, firstly peripheral nerve sheath tumour (Federici et al, 2015; Kappe et al, 2009; Lemonnier et al, 2022; Schneider et al, 2010) and granulomatous neuritis (Beltran et al, 2016). In light of this, imaging alone cannot reach a conclusive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main differentials for the mass seen on CT were neoplastic, inflammatory, or infectious. Previous case reports of horses with masses in close proximity with the cranial nerves have described multiple differing diagnoses, firstly peripheral nerve sheath tumour (Federici et al, 2015; Kappe et al, 2009; Lemonnier et al, 2022; Schneider et al, 2010) and granulomatous neuritis (Beltran et al, 2016). In light of this, imaging alone cannot reach a conclusive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of 64 horses with facial nerve dysfunction found that the most common cause was trauma, though multiple other aetiologies were described (inflammatory conditions, idiopathic, iatrogenic) and only one case of neoplasia (Boorman et al, 2020). There are scarce reports detailing cranial nerve dysfunction as a consequence of either direct or indirect neoplastic growth in the horse (Boorman et al, 2020; Federici et al, 2015; Kappe et al, 2009; Lemonnier et al, 2022; Schneider et al, 2010). This novel case report details the clinical, imaging and histopathological features of a squamous cell carcinoma (SCC) in an equine patient with trigeminal nerve dysfunction.…”
Section: Introductionmentioning
confidence: 99%